Use of Teaching Strategies in Higher Educational Institutions for Graduate Employability - Isgandarova, Aygun (ADA University, 2020)
University graduates in Azerbaijan currently face significant employability issues. Since 1993 to 2017 there was a steady decline in employment of students from 53% to 45%. The research shows that there are several reasons for this decline and teaching strategies is one of them. To understand this issue, I conducted a multi-phase study with the aim to investigate how universities cultivate graduate employability and the role of teaching strategies in this process. Three population groups, employers, university students, and university instructors participated in this study. The study was conducted at ADA University and partner organizations with ADA University. A total of 39 adults representing three population groups took part in my study. A multi-phase research design was employed, which consisted of three phases: qualitative study with employers, a mixed methods study with students, and a qualitative study with instructors. Data were collected using questionnaire, interview protocols, and focus group protocol. The findings obtained from the research allowed to claim that teaching strategies affect employability of graduates. Teachers use a variety of teaching strategies to enhance employability of graduates, which is confirmed by the results obtained from students. Students also think that they enter the job market with the certain set of skills and knowledge. However, according to employers these skills either are not adequate or do not fully meet the demands of current job market. This shows that there is a gap between job market and universities, which might be due to inadequate communication between these two parties. Thus, I recommend to strengthen the communication between the job market and universities in order to fully meet employers’ requirements. In addition to this, it is necessary to emphasize the role of teaching strategies for the growth of graduates’ employability skills by adopting internal policies. This also demands to support and increase university teachers’ capacity to cultivate graduate employability through various professional development events.
Keywords: Education; Education, Higher -- Azerbaijan.; Labor market -- Azerbaijan.; Teaching strategies -- Azerbaijan.; Education, Higher -- Azerbaijan.; Labor market -- Azerbaijan.; Employment, Graduates -- Azerbaijan.; University-industry collaboration -- Azerbaijan.